The Influence Of Transformational Leadership Style And The Work Environment On Employee Performance With Work Motivation As A Mediating Variable At The Population And Civil Registration Office Of Dairi Regency - Agus Raja Gukguk; Abdi Sugiarto (Yayasan Multidimensi Kreatif, 2025)
Employee performance is influenced by various factors, including transformational leadership style and work environment provided by the organization. An effective transformational leadership style and the right work environment can increase Motivation, which further contributes to improved performance. This study aims to identify the influence of transformational leadership style and work environment on employee performance by considering the role of Motivation as a mediating variable in the Population and Civil Registration Office of Dairi Regency. Data was obtained through a survey of employees with a quantitative approach and analyzed using the Partial Least Squares (PLS) method. The results of the analysis showed that transformational leadership style and work environment had a positive and significant influence on motivation, with T-Statistic values of 4.718 and 4.838, respectively, and P-Value of 0.000. Motivation is proven to have a positive and significant influence on Employee Performance with a T-Statistic value of 9.799 and a P-Value of 0.000, emphasizing the importance of Motivation as a performance driving factor. Indirect influence analysis shows that transformational leadership style and work environment significantly affect Employee Performance through Motivation, with an influence coefficient of 0.384. These findings indicate that improving transformational leadership style and work environment will be more effective in encouraging Employee Performance when facilitated by high motivation. Advice is provided to institutions to improve access to technology and training, as well as evaluate transformational leadership style strategies and existing work environments. Researchers are further encouraged to explore other mediating variables, such as organizational culture and psychological capital, in the context of performance improvement.